Chaiqin chengqi decoction ameliorates acute pancreatitis in mice via inhibition of neuron activation-mediated acinar cell SP/NK1R signaling pathways. (28th June 2021) - Han, Chenxia; Du, Dan; Wen, Yongjian; Li, Jiawang; Wang, Rui; Jin, Tao; Yang, Jingyu; Shi, Na; Jiang, Kun; Deng, Lihui; Fu, Xianghui; Mukherjee, Rajarshi; et al.
Abstract: Ethnopharmacological relevance: Chaiqin chengqi decoction (CQCQD) and its derivatives have been widely used in China for the early management of patients with acute pancreatitis (AP). Numerous studies demonstrate the anti-inflammatory and anti-oxidative effects of CQCQD and derivatives, but whether these effects can be attributed to suppressing neurogenic inflammation, has never been studied. Aim of the study: To investigate the effects of CQCQD on substance P (SP)-neurokinin 1 receptor (NK1R) based neurogenic inflammation in an experimental AP model. Material and methods: For AP patients on admission, pain score was accessed by visual analog scale (VAS); the levels of serum SP and expressions of pancreatic SP and NK1R were also determined. For in vivo study, mice received 7 intraperitoneal injections of cerulein (50 μg/kg) at hourly intervals to induce AP, whilst controls received normal saline injections. In the treatment groups, CQCQD (10 g/kg, 200 μl) was intragastrically given at the third, fifth, and seventh of the cerulein injection or the NK1R antagonist CP96345 (5 mg/kg) was intraperitoneally injected 30 min before the first cerulein administration. The von Frey test was performed to evaluate pain behavior. Animals were sacrificed at 12 h from the first cerulein/saline injection for severity assessment. Pharmacology network analysis was used to identify active ingredients of CQCQD for AP and pain. In vitro, freshly isolated pancreatic acinar cells were pre-treated with CQCQD (5 mg/ml), CP96345 (1 μM), or selected active compounds of CQCQD (12.5, 25, and 50 μM) for 30 min, followed by SP incubation for another 30 min. Results: The VAS score as well as the levels of serum SP and expressions of pancreatic SP-NK1R were up-regulated in moderately severe and severe patients compared with those with mild disease. CQCQD, but not CP96345, consistently and significantly ameliorated pain, pancreatic necrosis, and systemic inflammation in cerulein-induced AP as well as inhibited NK1R internalization of pancreatic acinar cells. These effects of CQCQD were associated with reduction of pancreatic SP-NK1R and neuron activity in pancreas, dorsal root ganglia, and spinal cord. Baicalin, emodin, and magnolol, the top 3 active components of CQCQD identified via pharmacology network analysis, suppressed NK1R internalization and NF-κB signal pathway activation in isolated pancreatic acinar cells. Conclusions: CQCQD ameliorated cerulein-induced AP and its associated pain via inhibiting neuron activation-mediated pancreatic acinar cell SP-NK1R signaling pathways and its active compounds baicalin, emodin, and magnolol contributed to this effect. Graphical abstract: Image 1